Salutogenesis: A sense of coherence and health among British military veterans exposed to impactful life challenges - the emergence of post-traumatic growth and positive deviance within a life-story approach [version 1; peer review: 3 approved] - Jacqueline Maria Dias; Muhammad Arsyad Subu; Nabeel Al-Yateem; Wegdan Bani-Issa; Fatma Refaat Ahmed; Mini Sara Abraham; Richard Mottershead; Mustafa Muhamad Habeb; Nafi Alonaizi (F1000Research, 2024)
Background This study sought to capture the perspectives and experiences of two sub-groups of military veterans, namely those who had previously been identified as offenders and those employed as practitioners within the criminal justice system in the United Kingdom. Methods The lead author undertook narrative inquiry in the form of life story research. The life stories of 17 in-depth interviews were conducted across England and Wales, allowing for insight into the lived experiences of two life story trajectories of the health of military veterans. Existing literature on salutogenesis, health, post-traumatic growth, and positive deviance has also been investigated. Results Life story interviews were transcribed verbatim and analyzed concurrently using thematic analysis to identify emergent themes. The researchers used thematic analysis as an analytical framework to allow descriptive themes from the literature on salutogenesis, health, post-traumatic, and positive deviance to be compared with those of life-story interviews. Conclusion The study adopts a salutogenic approach, which suggests that an important indicator for a sense of coherence is enabled through the positive utilization of resilience through the reconstruction of military identity and experience. Notably, the concept of salutogenesis demonstrates the ability to draw from internal and external resources as circumstances require, to survive, and because of this, the participants’ health is maintained or improved. Hence, adaptation was notable through the coherence identified by the identity of being a veteran noted between the two subgroups and represents a continuous and dynamic process. The study suggests that the development of a sense of coherence is not restricted to the early decades of life but is a continuous process as contexts, personal circumstances, and opportunities arise. This later point is realized through the presence of post-traumatic growth and positive deviance, as they aid in the nurturing and development of a renewed sense of coherence via the known identity of military service and life.